Phenomenological characteristics of autobiographical future thinking in nurses with burnout: a case-control study - Xue, Bowen; Feng, Yaping; Zheng, Jie; Li, Xin; Zhao, Yihui; Yang, Xiaoshan; Zhang, Yu; Wang, Shujin; Hu, Zhiguo; Luo, Hong (Frontiers in Psychology, 2023)
Objective: Nurses constitute the largest group of healthcare workers worldwide, and job burnout is very common among them. This study aims to explore abnormal future thinking in nurses with burnout. Additionally, the study investigates whether these manifestations worsen as burnout progresses.The study was conducted in inpatient ward nurses at a tertiary hospital in Hangzhou, China. In the first phase, two group of nurses were recruited: nurses with burnout (N = 70) and nurses without burnout (N = 70). In the second phase, three groups were recruited according to the burnout levels: mild burnout (N = 43), moderate burnout (N = 42) and severe burnout (N = 43). Data on job burnout were obtained using the Chinese Maslach Burnout Inventory. The Sentence Completion for Events in the Future Test (SCEFT) was employed to measure the content of future thinking, which was evaluated by two raters in terms of the specificity, emotional valence, and concrete content of the imagined future events. The proportions of specific types of events among all the produced events were calculated.The results revealed that nurses with burnout, compared to nurses without burnout, imagined fewer specific future events, positive events, and events related to relationships and achievement. They also had more omissions. As the level of burnout increased, their impairment in future thinking worsened. Furthermore, the results also revealed that the scores of emotional exhaustion, depersonalization, and personal accomplishment had significant correlations with the 2 proportions of positive events and events related to relationships and achievement/mastery in nurses' future thinking content.The future thinking ability of nurses with burnout was impaired, and this impairment worsened as the symptoms of burnout progressed. The findings of the present study have important implications for nurse caring and advocate effective interventions targeting positive future thinking to mitigate nurses' burnout.